Foregrounding in E.E. Cummings’ Your Little Voice: A Stylistic Analysis - Dangan, Susan (JPAIR Multidisciplinary Research, 2016)
Poetry defines and records the poet’s views, opinions, and society to whom he/she addresses (Biclar, 2014). The study was conducted to stylistically analyze E.E. Cummings’, Your Little Voice. Specifically, it answered the questions: what are the foregrounded parts in the poem of E.E. Cummings’ your little voice? At what linguistic levels do they occur? How do the foregrounded portions of the text relate together and contribute to the interpretation of the poem? Through the descriptive-qualitative research, employing the Practical Stylistic Analysis, the findings and interpretations revealed that E.E. Cummings’ your little voice is wholly foregrounded as a result of his choice to deviate from the linguistic norms and normal conventions of language. All the poetic lines in the poem exhibit absurdity and irregularity which made them difficult to understand. The linguistic deviations occur at graphological, lexical, grammatical, and semantic levels. There is a cohesion of foregrounding that contributes to the interpretation of the poem. By acting as links between themselves, all the items conferred a cohesive strength on the poem and make it functioned as a unified whole. The poem explains the persistent and strong desire of the poet for the addressee not within his immediate reach.